Overseas teaching and professional growth in the short-term international mobility program: Practical experiences and educational implications for preservice teachers in Taiwan - Lin, Hsien-Ming; Lin, Sheau-Wen; Lee, Ya-Ting (Journal of International Students, 2025)
This study examines the experiences, meanings, and professional development of preservice teachers at National Pingtung University (NPTU) in Taiwan who participated in a short-term international mobility program that involved overseas teaching in Kampar, Malaysia. Guided by the four educational competencies proposed by NPTU’s Suzaku Pioneer University Social Responsibility (USR) Project—professional competence, exploratory competence, practical competence, and caring competence—this qualitative study employed thematic analysis to examine data collected through semi-structured interviews, reflective reports, and teaching activity documentation. The findings indicate that although the short program duration limited the deepening of professional teaching knowledge, it significantly enhanced students’ exploratory, practical, and caring competencies. The participants developed greater sensitivity to cross-cultural educational contexts, improved their reflective teaching practices, and expressed stronger concerns for educational equity and social justice. The program also broadened their global perspectives and intercultural communication skills, particularly among those traveling abroad for the first time. This study highlights the importance of short-term international mobility programs in enhancing teacher education and concludes by discussing the study’s limitations and providing recommendations for future research.